Tailoring of Magnetocaloric Effect in Ni45.5Mn43.0In11.5 Metamagnetic Shape Memory Alloy. (9th February 2012) - Rosa, W. O.; González, L.; García, J.; Sánchez, T.; Vega, V.; Escoda, Ll.; Suñol, J. J.; Santos, J. D.; Alves, M. J. P.; Sommer, R. L.; Prida, V. M.; Hernando, B.
Abstract : We investigate the direct and inverse magnetocaloric effect in Ni45.5 Mn43.0 In11.5 Heusler alloy ribbons comparing the results obtained for the as-quenched sample with the ones after different annealing procedures. An enhancement and shift of the entropy maximum to near room temperature is observed in all annealed samples. A remarkable magnetocaloric effect is observed in samples with short-time treatment (10 minutes) and at the lowest annealing temperature. We show that the suppressing of uncompensated martensitic transition and thermal hysteresis are both influenced by the heat treatment. Also, an improvement on Curie's temperature is observed and, at low magnetic field, it has been risen up to 310 K. Our results demonstrate that the martensitic transformation is highly sensitive to the applied magnetic field and also to the annealing treatment, which means that the magnetocaloric effect can be tuned showing different behaviors for each sample.